2006
DOI: 10.1086/498112
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Percutaneous Bone Biopsy Specimens For Diagnosis of Diabetic Foot Osteomyelitis: Concordance With Ulcer Swab Cultures

Abstract: These results suggest that superficial swab cultures do not reliably identify bone bacteria. Percutaneous bone biopsy seems to be safe for patients with diabetic foot osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
207
4
20

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(238 citation statements)
references
References 22 publications
7
207
4
20
Order By: Relevance
“…In addition, it had to be confirmed by a positive culture of a transcutaneous bone biopsy performed after an antibiotic-free period of at least 2 weeks as described earlier by our group (10). Patients who had gangrene and who required bone resection because of bone and/or joint destruction or amputation due to severe peri-osteoarticular damage were not included.…”
Section: Populationmentioning
confidence: 99%
“…In addition, it had to be confirmed by a positive culture of a transcutaneous bone biopsy performed after an antibiotic-free period of at least 2 weeks as described earlier by our group (10). Patients who had gangrene and who required bone resection because of bone and/or joint destruction or amputation due to severe peri-osteoarticular damage were not included.…”
Section: Populationmentioning
confidence: 99%
“…In diabetic foot infections, the role of anaerobic bacteria is particularly unclear; some studies have reported that anaerobic bacteria play a minor role (20) (21) , while other studies found a high incidence of anaerobic bacteria (5) (22) .…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of this study is that data on the microbial isolates of the infections were not collected. We rarely take superficial swabs of wounds because they are unreliable culture specimens (51)(52)(53). Thus, most of our cultures were of deep tissue and therefore obtained only for the more severe wounds.…”
Section: Statistical Analysesmentioning
confidence: 99%